Etika Komunikasi Mahasiswa pada Dosen di Media Sosial Whatsapp - Reynaldi Reynaldi; Das’ad Latief; Kamaluddin Tajibu (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
The study aims to provide an understanding of students about the importance of communication ethics in WhatsApp towards lecturers within the scope of the lecture room, looking deeper into the rules that students need to understand regarding the ethics of communicating with lecturers on WhatsApp. This research uses descriptive qualitative research methods, with a case study. The theory used in the article uses the theory of politeness strategy. Results showed that the rapid development of information brought changes in the form of communication between students and lecturers. The development makes every form of system that occurs in the world of lectures change, especially in contacting lecturers, formerly directly, now online. however, students often do not understand the ethics of communicating with lecturers on WhatsApp, so it needs to be emphasized and underlined by students within the scope of lectures. 7 basic ethics are important for students to understand in contacting lecturers on WhatsApp for the benefit of lectures, namely: 1) The right time, 2) Opening and closing greetings, 3) Apologize first, 4) Introduce yourself, 5) Using formal language 6) Follow the rarities, and 7) Rules that can be understood in the ethics of communicating with lecturers through WhatsApp media.